1983
DOI: 10.1007/bf02498719
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the patella treated by operation

Abstract: A retrospective analysis of 93 operatively treated fractures of the patella is presented. Tension band fixation was used in 14, circumferential wire in 15 and screw fixation in 19 patients. Partial patellectomy was performed in 35 cases and total patellectomy in 10 cases. The result was considered excellent in 27% of the patients, good in 49%, fair in 16% and poor in 8%. Patients under 30 years of age had better results than the older ones (p less than 0.01). Tension band fixation gave results superior to scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
4

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 13 publications
0
45
0
4
Order By: Relevance
“…This increase in quadriceps force may be beyond the capacity of some patients, particularly those with long-standing intra-articular disease, advanced age, high activity demands, and an extensor lag before surgery. Anterior tension band wiring appears to restore excellent functional integrity in approximately 86% of patients with very low complication rates [2,10]. The complications most commonly reported were infection, loss of motion, hardware-related problems, refracture, and delayed union or nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in quadriceps force may be beyond the capacity of some patients, particularly those with long-standing intra-articular disease, advanced age, high activity demands, and an extensor lag before surgery. Anterior tension band wiring appears to restore excellent functional integrity in approximately 86% of patients with very low complication rates [2,10]. The complications most commonly reported were infection, loss of motion, hardware-related problems, refracture, and delayed union or nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Patellar fractures account for approximately 1% of all the fractures, and males are affected twice as often as females. 3 The injury mechanism may be either direct or indirect, and direct trauma is the most common. Additionally, patella fractures can also occur as complications after a total knee replacement surgery or patellar tendon graft transplantation.…”
mentioning
confidence: 99%
“…In a series by LeBrun et al, patients with operatively treated patella fractures were shown to have poor physical health and knee functional scores, likely related to the development of osteoarthritis [3]. Alternatively, other studies have shown excellent outcomes following surgical fixation of patella fractures, with patients returning to full function by 12-months [12][13][14][15]. The results of this study show that there is no effect on TKA revision free survival, regardless of operative versus nonoperative treatment.…”
Section: Discussionmentioning
confidence: 73%